Certyfikat szczepionkowy jako instrument prawnej regulacji międzynarodowego ruchu osobowego - Narożniak, Agnieszka; Princ, Marcin (Studia Prawa Publicznego, 2022)
The SARS-CoV-2 pandemic affected almost all the inhabitants of the globe, and mi-grants were among those who felt it particularly hard. Their problems were largely related to numerous limitations in the international movement of persons. As part of the ﬁght against these effects, national governments have initiated a discussion on the idea of launching vaccine certiﬁcates, sometimes called “Covid passports”. The concept has been developed and has led to the adoption of speciﬁc solutions in various countries, as well as on a wider, regional scale, in particular in the form of the EU digital COVID certiﬁcate. In the paper, the authors outline individual concepts and consider whether a vac-cine certiﬁcate does indeed bear the features of a travel document and whether it is justiﬁed to use this term. They go on to contrast the idea of issuing such certiﬁcates with national, EU and regional law. Finally, they reﬂect on what formal and material conditions must be met by such a document in order to enable the holder to cross borders, and whether such tools can be reused in the event of future pandemics. The research allows several conclusions to be formulated. The EU digital COVID certiﬁcate or other certiﬁcates cannot be regarded as travel documents, in particular, they cannot be called passports. Vaccine certiﬁcates are not meant to be a privilege or a restriction, but only an instrument that allows possible restrictions in the international movement of persons to be waived for the holder of the document (assuming that the restrictions themselves are not illegal). They should be consid-ered a temporary measure, applied in extraordinary circumstances as an instrument in the hands of states or state organizations, not private entities. In such a formula, they can also be used in the event of similar epidemic threats in the future.